A prospective study of myoconjunctival enucleation for enhanced implant motility - Asari, Wilhemina A.; Rawat, Supriya; Siddhpura, Nirali P. (International Journal of Research in Medical Sciences, 2021)
Background: After enucleation rehabilitation and cosmesis remain the nemesis of an enophthalmic socket, the cosmetic goal is to replace the lost volume of the socket and to restore natural appearance and movement with an artificial eye. The aim of this is to determine implant motility after myoconjunctival enucleation technique. Methods: The study was conducted in 35 patients who underwent myoconjuctival enucleation at M and J Western Regional Institute of Ophthalmology, Civil Hospital, Ahmedabad from the period November 2019 to December 2021. Simple random sampling method was used and subjects were selected based on the inclusion and exclusion criteria. All patients were evaluated on 1st post-operative day, 1st week, 4th week and 12th week of surgery. Post-operative results were compared on the follow-ups in terms of motility index. Results: Average motility index (sum of medial movement, lateral movement, upward movement and downward movement divided by 4) of the 35 patients measured after first week of surgery was 3.2 mm, which was 3.21 mm in 4th week and at 12th week it was 3.23 mm. Conclusions: In contrast to conventional enucleation technique, in myoconjunctival enucleation technique each rectus is sutured to the respective fornix thus preventing stretching, increasing implant stability and motility. Thus it is considered procedure of choice in primary enucleation.